2009
DOI: 10.1590/s0074-02762009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotominae distribution in Janaúba, an area of transmission for visceral leishmaniasis in Brazil

Abstract: In Brazil, visceral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
33
2
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 23 publications
16
33
2
7
Order By: Relevance
“…Nevertheless, no numeric difference was found between female and male Lu. L. longipalpis, in contrast to previously published studies reporting male predominance (XIMENES et al, 2000;BARATA et al, 2005;MICHALSKY et al, 2009;QUEIROZ et al, 2009). This finding also contrasts with that of a monitoring survey previously performed in Mossoró (AMÓRA et al, 2010) that found a higher number of female flies.…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…Nevertheless, no numeric difference was found between female and male Lu. L. longipalpis, in contrast to previously published studies reporting male predominance (XIMENES et al, 2000;BARATA et al, 2005;MICHALSKY et al, 2009;QUEIROZ et al, 2009). This finding also contrasts with that of a monitoring survey previously performed in Mossoró (AMÓRA et al, 2010) that found a higher number of female flies.…”
Section: Resultscontrasting
confidence: 75%
“…The districts studied are located in the periphery of the city, with abundant vegetation, domestic animals and organic matter, creating favorable conditions for sand fly breeding and population growth, corroborating XIMENES et al studies (2000). These conditions are known to favor the presence of L. longipalpis (MICHALSKY et al, 2009), the predominant phlebotomine species in the city. Similar results were found in a previous monitoring survey by the same research group (AMÓRA et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…longipalpis accounted for more than 97% of all sandflies captured and was by far the most predominant sandfly species in the investigated peridomicile and intradomicile areas. This vector has also been found to be the principal Lutzomyia species in other endemic areas (Araújo et al 2000, Ximenes et al 2000, Michalsky et al 2009). Lu.…”
Section: Discussionmentioning
confidence: 95%
“…In Porteirinha (15 o 44'42''S, 43 o 01'46''W), higher densities of L. longipalpis have been observed during the rainy season and rainfall was the major variable accounting for predicting the L. longipalpis captured . In Janaúba (15°47'50″S, 43°18'31″W) and Várzea Grande (15 o 32'30''S, 56 o 17'18''W), marked and slight increases in population have been observed immediately after rainfall (Missawa & Dias 2007, Michalsky et al 2009). …”
Section: American Visceral Leishmaniasis (Avl) Is a Zoonosis Caused Imentioning
confidence: 99%